Experimental and numerical comparisons of self-reacting point absorber wave energy converters in regular waves. (1st August 2015) - Beatty, Scott J.; Hall, Matthew; Buckham, Bradley J.; Wild, Peter; Bocking, Bryce
Abstract: An experimental and numerical comparison of the performance of two self-reacting point absorber wave energy converter designs is undertaken for heave motions. The designs are either currently, or have recently been, under development for commercialization. The experiments consist of a series of 1:25 scale model tests. The physical model features a re-configurable reacting body shape, a feedback controlled power take-off, and a heave motion constraint apparatus. Detailed descriptions of the reconfigurable model design, the analysis/test methodologies, and power capture are given. An extension of Budal׳s theoretical upper bound on power capture for application to self-reacting point absorbers is proposed. A quantitative comparison is made of the two self-reacting point absorber designs in terms of displacement, power take-off force requirements, and power capture in typical (non-extreme) operating conditions with reference to theoretical upper bounds. The design implications of a reactive power take-off control scheme and relative motion constraints on the wave energy converters are investigated using an experimentally validated numerical dynamics model. Abstract : Highlights: Two self-reacting point absorber WEC designs are compared in regular waves. 1:25 scale physical models of the WECs with feedback controlled PTOs are developed. Budal׳s upper bound on power capture for one body WECs is extended to two body WECs. A frequency domain model is validated by power capture and dynamic motion in heave. The effects of motion constraints and reactive control are investigated.